The Comparison of Giardia lamblia Infection and Nutritional Status of Elementary School Students in Mandangin Island, Sampang and Mojo Village, Surabaya, Indonesia - Zaidan Arifiansyah Bachtiar; Amalia Putri Uswatun Hasanah; Muhammad Yasin; Rahmadany Isyaputri; Budiono Budiono; Sukmawati Basuki (Faculty of Medicine, Universitas Airlangga, Surabaya, Indonesia, 2020)
Introduction: Giardia lamblia infection can cause impaired absorption of nutrientsand affects to the nutritional status that has not yet fully investigated in Indonesia.This study aimed to investigate the comparison of prevalence of Giardia lambliainfection and nutritional status of elementary students in Mandangin island and Mojovillage where were different condition.Methods: An analytical observational study with cross sectional design wasconducted in Mandangin island in July 2017 and Mojo village in June 2018 byinformed consent. Stools of elementary students were collected for Giardia lambliaidentification under a light microscope using direct smear method. Nutritional statusof students were determined by body mass index (BMI), and categorized as severeunderweight, underweight, healthyweight, overweight, and obese.Results: Forty-five stools samples were collected from elementary students inMandangin island and 55 stools samples in Mojo village. Prevalence of Giardialamblia infection without symptoms was higher in elementary students in Mandanginisland than Mojo village (28,9%, 13/45 and 1,8%, 1/55, respectively). Giardiasisprevalence in Mandangin island was significantly difference with Mojo village(p<0.0001, chi square-test). Nutritional status of students in both study sites showeddominant healthy-weight that were 73.3% (34/55) in Mandangin island and 61.8%(33/45) in Mojo village. Giardiasis was commonly observed in students with healthy-weight and it was higher in Mandangin island (8/33, 24.2%) than Mojo village (1/34,2.9%).Conclusion: Asymptomatic giardiasis was highly found in elementary students inMandangin island and commonly observed in students with healthy-weight from both 3 regions. It suggested that asymptomatic giardiasis might not affect to the nutrition status of students.